Arthroscopic Treatment of Symptomatic Discoid Lateral Meniscus and Nondiscoid Meniscus in Adolescent Patients. Issue 14 (December 2022) - Su, Lisa; Bennett, Abbie; Combs, Kristen; Torrez, Timothy W.; Pham, Derek C.; Jackson, Nicholas J.; Bowen, Richard E.; Beck, Jennifer J.
Background: Discoid lateral meniscus (DLM) is a rare condition. Patient-reported outcomes using validated instruments are underreported in the literature. DLM outcomes have not been directly compared with nondiscoid meniscus (non-DLM) in adolescent patients. Purpose/Hypothesis: This study sought to analyze the difference in patient characteristics, surgical treatment, and patient-reported outcomes for adolescent patients arthroscopically treated for symptomatic DLM and non-DLM pathology. We hypothesized that DLM and non-DLM patient-reported outcomes would be similar. Study Design: Cohort study; Level of evidence, 3. Methods: A retrospective review of patients aged <18 years with symptomatic DLM and non-DLM pathology was completed between 2015 and 2021 at a single academic institution. Chart reviews for patient characteristics and surgical operative indications and technique were completed. Patient-reported outcome scores were prospectively collected preoperatively and at 6 months, 1 year, and 2 years after surgery. Results: Patients in the DLM group (n = 48), when compared with the non-DLM group (n = 45), were younger (12.71 vs 15.78 years, respectively; P < .001) and had lower body mass index (24.53 vs 28.91, respectively; P < .02). Both groups were majority Hispanic and more commonly male (DLM 65% vs non-DLM 60%). All of the DLM patients had surgery on the lateral discoid meniscus (n = 48), whereas the non-DLM group had surgery on the lateral meniscus (n = 37), medial meniscus (n = 7), or both (n = 1). A majority of patients in both groups underwent meniscal repair (DLM 73% and non-DLM 62%), and there was no difference in surgical treatment between groups ( P > .05). A statistically significant improvement was seen in International Knee Documentation Committee (IKDC) and Physical Activity Questionnaire (PAQ) scores from the preoperative assessment to 6 months, 1 year, and 2 years after surgery for both DLM and non-DLM groups ( P < .05). No difference was found in scores between DLM and non-DLM groups, between sexes, or between age groups (<13 years or ≥13 years) ( P > .05). Conclusion: Although patients with DLM were younger and had lower body mass index, the IKDC and PAQ scores were not significantly different between the DLM and non-DLM groups. Both groups showed a significant improvement in scores relative to their preoperative scores. Sex and age did not affect IKDC or PAQ scores.